(untitled) (Politeja, 2024)
The article’s primary goal is to define how establishing the European Green Deal (EGD) development strategy has influenced changes in the European Union’s (EU’s) regional policy programming and implementation. The subject of the analysis is the objectives and financial instruments of the EU regional policy for the years 2021-2027, which have been programmed taking into account the priorities defined in the EGD strategy. The article will verify the hypothesis regarding the impact of the EU’s strategic principles on the paradigm shift in the EU regional policy. European Union development priorities focused on climate neutrality, environmental protection, and biodiversity require implementing a regional policy centred on specific horizontal goals common to all EU regions. The author argues that as a result, the territorial aspect of implementing the EU regional policy weakens, reflected in the arrangement of its goals and the directions of intervention of structural funds in the Multiannual Financial Framework (MFF) 2021-2027.